Equation not balancing

I have the following expression: (3a^-2 * b)/(-3a^2).  To my understanding this expression can be simplified to (-a^-4 * b) because:
3/3 = 1
a^-2/a^2 = a^-4
b remains the same
When I substitute actual values for the variables the equation doesn't balance.
a=2, b=4
-(3a^-2 * b)/(-3a^2) = -a^-4 * b
-(3(0.25)(4))/(-3(4)) = (0.0625)(4)
-3/-12 = 0.25
-0.25 = 0.25
Why is there a polarity difference?  What am I not understanding?
NevSoFlyAsked:
Who is Participating?
I wear a lot of hats...

"The solutions and answers provided on Experts Exchange have been extremely helpful to me over the last few years. I wear a lot of hats - Developer, Database Administrator, Help Desk, etc., so I know a lot of things but not a lot about one thing. Experts Exchange gives me answers from people who do know a lot about one thing, in a easy to use platform." -Todd S.

byundtMechanical EngineerCommented:
Double-check step 1 in your simplification. You should have a minus sign on the bottom.

(3)/(-3) = -1
byundtMechanical EngineerCommented:
And when you plugged values into the original equation, you put a minus sign in two places on the left side, where the original expression only had 1.
NevSoFlyAuthor Commented:
I'm sorry both of those were typos.  The steps should be as below.  The equation still doesn't balance.

•(3a^-2 * b)/(-3a^2) = -a^-4 * b


•(3(0.25)(4))/(-3(4)) = (0.0625)(4)


•3/-12 = 0.25


•-0.25 = 0.25
Rowby Goren Makes an Impact on Screen and Online

Learn about longtime user Rowby Goren and his great contributions to the site. We explore his method for posing questions that are likely to yield a solution, and take a look at how his career transformed from a Hollywood writer to a website entrepreneur.

Enabbar OcapCommented:
You have a minus sign on the right hand side at -a^-4*b but you lose it when you get to (0.0625)(4).
The minus value should still be there.
The negative you might think you are losing is the index, not the value. The negative index just means 1/(value with positive index)

Experts Exchange Solution brought to you by

Your issues matter to us.

Facing a tech roadblock? Get the help and guidance you need from experienced professionals who care. Ask your question anytime, anywhere, with no hassle.

Start your 7-day free trial
byundtMechanical EngineerCommented:
[3a^-2*b]/(-3a^2) = -a^-4*b

Plug in a = 2 and b = 4
[3*4/(2^2)] / (-3 * 2^2) = -4/(2^4)

[3*4/4] / (-3*4) = -4/16

[3]/(-12) = -.25

-.25 = -.25
Enabbar OcapCommented:
An example in case it helps:
You have -3a^2 which comes out to -3*2^2 = -12, but on your right hand side you have
-a^-4 which could be written as -1a^-4 = -1*0.0625 = -0.0625.
Hope this helps.
NevSoFlyAuthor Commented:
That was right in front of my face and I didn't see it,  Thanks.
It's more than this solution.Get answers and train to solve all your tech problems - anytime, anywhere.Try it for free Edge Out The Competitionfor your dream job with proven skills and certifications.Get started today Stand Outas the employee with proven skills.Start learning today for free Move Your Career Forwardwith certification training in the latest technologies.Start your trial today
Math / Science

From novice to tech pro — start learning today.